Digitalisasi Fesyen Lokal Menggunakan Digital Entrepreneur Indicator (DEI) Pada Butik UMKM Di Kuningan Jawa Barat - Gunawan, Casssandra; Jennifer; Siahaan, Sapna; Trilaksono, Teddy; Purusottama, Ambara (J-Dinamika : Jurnal Pengabdian Masyarakat, 2025)
This Community Development (Comdev) Universitas Prasetiya Mulya aims to facilitate the Dzanira Collection fashion business located in Cilimus Village, Kuningan, West Java. The main challenges the MSME partners face are the lack of a dedicated boutique to display their clothing products and the absence of a suitable location for catalog photo shoots that can be shared on social media platforms. In response to these challenges, the comdev group solution involved creating a 1.5m x 1.5m booth inside the MSME partner's home, which serves as both a product photo shoot area and a physical retail space for offline sales to visitors. By creating an elegant boutique-like atmosphere, the comdev group not only anticipates attracting more visitors to the MSME partner's home but also providing a professional environment to showcase their products, enhancing the project's credibility. The results of this activity are an increase in the marketing skills of the group partners and a 60% growth in sales. Through this initiative, the group aims to empower MSME entrepreneurs like the MSME partners to improve their business operations and adapt to changing market dynamics